KOPDAS (Smart Puzzle Comic) AS A READ-ALOUD-BASED LITERACY MEDIUM FOR ENHANCING ELEMENTARY SCHOOL STUDENTS’ READING INTEREST - Lirra Zanni; Arina Restian; Nurul Zuriah (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to develop an innovative learning medium, KOPDAS (Smart Comic Puzzle), as a literacy tool based on read-aloud activities to foster reading interest among elementary school students and to examine its effectiveness. The background of this research stems from students' low interest in reading, driven by the lack of engaging learning media and the underutilization of reading corners in schools.Methodology – The study employs the Research and Development (R&D) method, using the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The research subjects include material experts, media experts, and second-grade students at SD Negeri Maron Kulon 1 in Probolinggo Regency. Data were collected through observation, interviews, validation questionnaires, and product trials, with pre-tests and post-tests.Findings – KOPDAS is effective at enhancing students' reading interest. This medium combines comic visuals with puzzle-solving activities featuring Pancasila symbols, thereby increasing active participation, concentration, and comprehension of reading content. The use of read-aloud techniques also helps improve understanding, pronunciation, and students' confidence in reading. The development of KOPDAS is expected to serve as a reference for the innovation of literacy learning media, creating a fun, communicative, and interactive learning atmosphere.Contribution – This research contributes to the development of an innovative literacy medium, KOPDAS (Smart Comic Puzzle), designed using the read-aloud approach to enhance elementary students' interest and reading habits. The medium integrates the visual and interactive elements of comics and puzzles while strengthening foundational literacy skills through engaging read-aloud activities. Furthermore, this study makes a practical contribution to teachers by offering an alternative literacy learning medium that is creative, appealing, and well-suited to the learning characteristics of young learners.